2019
DOI: 10.1007/s11187-019-00161-w
|View full text |Cite
|
Sign up to set email alerts
|

Firm bribery and credit access: evidence from Indian SMEs

Abstract: This study investigates the effect of paying bribes on access to credit for small, and medium enterprises (SMEs). Bribery is variously portrayed in the literature as greasing the wheel (helping) or sand in the wheel (impeding) when applying for credit leaves the issue unresolved. Using The World Bank Enterprise Surveys of SME data, an answer for India emerges using an instrumental variable probit model. SME bribery is detrimental to accessing credit and more so for firms that have been in business for many yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 79 publications
1
49
0
Order By: Relevance
“…Another important factor is bribery that may take place during the lending process through bribing bank officials [48]. It was shown that bribery plays a crucial role in determining the ability of firms to access to financial services [49][50][51]. The previous papers also included sector and export as dummy variables to test whether there is a difference in accessibility to finance between export and non-export enterprises.…”
Section: Psm Coupled With Did (Psm-did)mentioning
confidence: 99%
“…Another important factor is bribery that may take place during the lending process through bribing bank officials [48]. It was shown that bribery plays a crucial role in determining the ability of firms to access to financial services [49][50][51]. The previous papers also included sector and export as dummy variables to test whether there is a difference in accessibility to finance between export and non-export enterprises.…”
Section: Psm Coupled With Did (Psm-did)mentioning
confidence: 99%
“…Entrepreneurs could receive special and beneficial treatment by engaging in corruption, such as bank loans, permit approvals, direct contracts and regulation favours (Acquaah, 2007;Dheer, 2017;Wellalage et al, 2019aWellalage et al, , 2019b. Further, entrepreneurs in developing countries have limited alternate opportunities to earn income (Ahsan et al, 2020), which may compel them to engage in bribery and other forms of corruption (e.g., circumventing tax and business laws) to succeed.…”
Section: Institutions and Corruptionmentioning
confidence: 99%
“…However, owners/CEOs of SMEs need to have sufficient financial resources to engage institutional ties and develop good relationships with them, as such connections are often developed by socialising in the same circles (Barton, 1985;Davis et al, 2003;Maclean et al, 2010Maclean et al, , 2017. The challenge of accessing credit in environments where corruption is prevalent (Wellalage et al, 2019a) makes financial slack even more valuable. Next, we explain the hypothesised relationships among the variables in the model.…”
Section: Institutions and Corruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides firm size, credit rationing and its negative returns on firms' productivity may be related to the context in which firms are located and operate. The literature has widely underlined how national macroeconomic conditions, the development and regulation of the national financial sector, and the quality of national institutions are fundamental factors influencing both firms' access to credit (Andrieu et al, 2018; Canton et al, 2013; Hewa Wellalage et al, 2019) and performance (Aidis, 2005; Bowen & De Clercq, 2008; Dollar et al, 2005; Dutta & Sobel, 2016). By contrast, how regional institutions influence firms' productivity, in general, and the credit constraints–productivity relationship, in particular, has received limited attention.…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 99%